PENINGKATAN KETERAMPILAN MEMBACA PERMULAAN MELALUI MEDIA PIAS-PIAS KATA PADA PESERTA DIDIK KELAS 1 SDN WONOKALANG - Siti Asnipah; Meirza Nanda Faradita; Iswayuni (PROCEEDING UMSURABAYA, 2024)
This research is motivated by students who are not yet able to read at first. Some students still have difficulty distinguishing letters, their pronunciation is not correct and there are still many students who still spell. The problem found in this research can be said to be the lack of initial reading skills in class I students at SDN Wonokalang. The causal factors, apart from internal factors, are also external factors, namely the media and learning models used by teachers which are still less attractive. This research aims to improve beginning reading skills by using word choices in class I elementary school. This research is classroom action research which consists of two cycles, the data taken is teacher observation data carried out in each learning process using word combinations as media. This research was carried out in 4 stages, namely planning, implementation, observation and reflection. The results of this research show that using word-pias media can improve the reading skills of first grade elementary school students. The results of observations of students' reading skills showed an increase, as evidenced by the fact that in cycle I the reading skills were 62. 5% and had not reached a minimum of 75% of all students in the class. And it increased in cycle II to 87. 5%, reaching a minimum of 75% of all students in the class. It can be concluded that the use of pias-pias words can improve the initial reading skills of first grade elementary school students.